Geographies of superstition, myths, freedom: Ibsen and Northern Norway - Torrissen, Wenche (Nordlit, 2015)
Ibsen visited Northern Norway only once in his lifetime and this was in the summer of 1891. Despite this fact, Ibsen was preoccupied with the North both as symbolic and geographical locations throughout his whole literary career. Why? This article will explore how the North is represented in Ibsen’s prose plays. It will assess whether Ibsen contributed to confirm already existing images of the North or whether he contributed to the construction of new images. The article will also explore how Ibsen used images of the North to construct meaning for contemporary audiences.